Genetical analysis of a diallel cross in cowpea - Teófilo, Elizita Maria (2014)
Four varieties of cowpea were crossed in all possible combinations, including the reciprocals. The genetic analysis was carried out according to the methodology of (Hayman 1954), Mather & Jinks (1971) and Griffing (1956). The characters studied were; number of pods per plant, pod length, weight of 100 seeds and yield per plant. The values of heterosis for yield per plant varied from 1.65 to 78.59% with a mean value of 34%. Of the four yield components studied, the character of pods per plant exhibited the highest values of heterosis, varying from 0.22 to 43.80% and a mean of 18.67. The non additive genetic variance was found to be significant for the characters such as the yield per plant, seed number per pod, while the additive genetic variance was observed in the case of pods per plant, pod length, and weight of 100 seeds.